Pengurangan Bullwhip Effect pada Rantai Pasok Air Minum Dalam Kemasan Menggunakan Metode Collaborative Planning, Forecasting, and Replenishment (CPFR): Studi Kasus - Muhammad Qadafi; Endang Suhendar; Aliffia Teja Prasasty (Universitas Mercu Buana, 2022)
CV Tirta Alam Dodu is a privately owned company engaged in the beverage industry in the form of AMDK. The problem faced by the company is that there is a difference between demand and sales, or better known as the bullwhip effect problem. The purpose of this study is to reduce the bullwhip effect on the supply chain and optimize the amount of product inventory according to the amount of demand. The method used is the Collaborative Planning, Forecasting, and Replenishment (CPFR) method. Based on the results of the research conducted, it can be concluded that the analysis of demand forecasting calculations on AMDK products at CV Tirta Alam Dodu was carried out using historical data on product demand through five analytical methods, including Linear Trend, Moving Average, Exponential Smoothing, Decomposition, and Winter's Model. The best forecasting resulted in Winter's Model which showed the smallest error value compared to the other four models. The way to minimize so that it does not become a bullwhip effect is to use the CPFR method, where the bullwhip effect value is obtained on glass mineral water products and gallons of mineral water of 0,985 and 0,898, respectively. This result shows that there is no amplification of demand and has reached the company's target, which is to fall below number one. The way to optimize inventory so that there is no excess stock or shortage of stock in the product is to make the amount of inventory based on the amount of demand from the forecasting results plus the safety stock.